COGNITIVE CONTEXTUAL MODEL IN AMERICAN POLITICAL DISCOURSE - Ramila Huseynova Farman kyzy (International Journal of Innovative Technologies in Social Science, 2025)
This article explores the cognitive contextual model within American political discourse, focusing on its role in shaping public perceptions, constructing societal ideologies, and facilitating effective communication between political figures and the public. Employing cognitive-discursive analysis, the study investigates how linguistic strategies, such as framing, metaphorical constructs, emotional appeals, and repetition, are utilized in political speeches to influence public opinion and advance political agendas. The research is grounded in an interdisciplinary approach, integrating insights from cognitive linguistics, discourse analysis, and political science. The analysis of public speeches by U.S. presidents highlights the interplay between language, cognition, and context, emphasizing the importance of shared knowledge and cognitive structures in understanding political messaging. By developing a cognitive contextual model, the study identifies key elements such as macro-level goals, micro-level linguistic features, and the implicit and explicit mechanisms that underpin political discourse. This research contributes to the fields of discourse studies and political communication, providing a comprehensive framework for analyzing the cognitive and contextual dimensions of political language and offering practical applications for enhancing communication strategies in political contexts.